The Quality of Apis Mellifera Honey from Sungai Mandau Subdistrict, Siak Regency Based on the Duration of Water Content Reduction: Kualitas Madu Apis Mellifera dari Kecamatan Sungai Mandau Kabupaten Siak Berdasarkan Lama Pengurangan Kadar Air - Tri Ratnaningsih*, Ambar; Romadlon , Hanapi; Novia Yanti, Rina (Universitas Lancang Kuning, 2025)
One of the non-timber forest products from the animal group that is widely utilized by communities today is honey. Communities around the Acacia crassicarpa plantation forests utilize these plants as a food source for Apis mellifera bees. The honey produced generally has a high moisture content, which affects its quality. Efforts are needed to reduce the moisture content of honey using a vacuum evaporator to meet the Indonesian National Standard (SNI) for honey quality. The research method was experimental, using honey samples from Sungai Mandau Subdistrict, Siak Regency, Riau Province. Moisture content reduction was carried out using a vacuum evaporator at a temperature of 40°C for 0, 12 and 24 hours. The honey that had undergone moisture reduction was tested for quality in accordance with SNI 8664:2018. Honey that had undergone moisture reduction for 12 hours had a moisture content of 19.15%, specific gravity of 1.434, diastase enzyme activity of 11.75 DN, hydroxymethylfurfural (HMF) content of 0.21 mg/kg, total sugar content of 75.53 °Brix, ash content of 0.162% w/w, acidity of 47.33 ml NaOH/kg, and insoluble solids of 0.57% w/w. Meanwhile, honey that had undergone moisture reduction for 24 hours had a moisture content of 17.59%, specific gravity of 1.482, diastase enzyme activity of 9.43 DN, HMF content of 0.67 mg/kg, total sugar content of 76 °Brix, ash content of 0.676% w/w, acidity of 44.43 ml NaOH/kg, and insoluble solids of 0.59% w/w.